2005
DOI: 10.1111/j.1365-2672.2005.02694.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and biochemical changes in pearl spot (Etroplus suratensis Bloch) stored under modified atmospheres

Abstract: Aims: This study aimed to determine the effect of packaging [air, modified atmosphere (MA)] on microbial growth, sensory and chemical parameters and also on shelf life of fresh pearl spot (Etroplus suratensis Bloch) and on the selection of microbial association. Methods and Results: Fresh pearl spot (whole, gutted) were packaged under both 100% air and MAs (40%CO 2 / 60% O 2 , 50%CO 2 /50%O 2 , 60% CO 2 /40%O 2 , 70% CO 2 /30% O 2 and 40% CO 2 /30% O 2 /30% N 2 ) and stored at 0°C. Microbial growth (counts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 28 publications
5
15
0
3
Order By: Relevance
“…pH values for whole ungutted trout samples increased with storage time from an initial value of 6.74 (Table 2) indicating bacterial growth and production of volatile basic compounds such as ammonia by fish spoilage bacteria. Increase in pH due to accumulation of alkaline compounds through autolytic activities and microbial metabolism has been reported in earlier studies [65,73,74]. Many microbes including Pseudomonas produce ammonia during amino acid metabolism.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…pH values for whole ungutted trout samples increased with storage time from an initial value of 6.74 (Table 2) indicating bacterial growth and production of volatile basic compounds such as ammonia by fish spoilage bacteria. Increase in pH due to accumulation of alkaline compounds through autolytic activities and microbial metabolism has been reported in earlier studies [65,73,74]. Many microbes including Pseudomonas produce ammonia during amino acid metabolism.…”
Section: Resultsmentioning
confidence: 93%
“…TMAO quantity in fish varies with the species and the environment. A wide range of TMA-N values have been reported by several investigators as acceptability limit i.e., 1-5mg N/100 g [62][63][64][65]. Sikorski et al [66] and Dalgaard et al [67] reported that a population of 108-109 cfu/g of S. putrefaciens was considered crucial for TMA production.…”
Section: Resultsmentioning
confidence: 99%
“…(1990) reported that a mixture of 80% CO 2 and 20% O 2 was more beneficial in extending the shelf life of Catla catla , and total viable counts were significantly higher in fish stored under air than that stored under MAP. Lalitha et al. (2005) reported a delay in the growth of aerobic bacteria in pearl spot packaged under gas mixtures 60% CO 2 : 40% O 2 and 70% CO 2 : 30% O2.…”
Section: Resultsmentioning
confidence: 99%
“…In India, research on MAP of freshwater as well as marine fish were carried out (Gopal et al. 1986, 1990, 1996; Lalitha et al. 2005).…”
Section: Introductionmentioning
confidence: 99%
“…There is little information on the effect of MAP with elevated O 2 level on bacterial growth retardation in the literature. Based on microbiological, chemical and sensory analyses, Sivertsvik Sankar et al (2008) and Lalitha et al (2005) examined the effect of various modified atmospheres on pearl spot, including a 60% O 2 /40% CO 2 atmosphere. During storage they detected a microbial growth decrease resulting in a longer shelf life when compared to air packaging.…”
Section: Discussionmentioning
confidence: 99%